Cloud Computing for Urban Transportation Syste - Angga Laksana, Eka (International Journal of Psychosocial Rehabilitation, 2020)
Todays with the rapid growth of city, transportation is becoming more complex environment. People face different problem on their daily life while by going to work, study, recreation etc. Hence, transportation play a vital role by carrying people from one place to other. Government need to solve transportation problem like traffic jam to make people can travel effectively. Not only government responsibility, but also people needs to participate because they share the same public infrastructure. Different type of cloud computing can become used to minimize the impact of traffic jam. This paper describes different type of cloud computing including the environment to build one. We also describe several challenges in order to implement cloud computing in urban transportation system.